An Unusual Ovarian Mucinous Borderline Tumor with a Large Solid Component. (22nd May 2019) - Kozawa, Eito; Inoue, Kaiji; Yano, Mitsutake; Yasuda, Masanori; Hasegawa, Kosei; Tanaka, Junji; Ichikawa, Tomoaki; Niitsu, Mamoru
Abstract : Herein, we report magnetic resonance imaging (MRI) findings of a mucinous borderline tumor of the ovary, which we observed as a mainly solid tumor with large solid components in the lower pelvic cavity. The appearance of ovarian epithelial tumors on imaging is often complex. Cystic to solid appearing masses may be observed, and they often resemble epithelial carcinoma. Due to mucinous or hemorrhage components of packed small or microcystic components, MRI depicts slightly high signal intensity on T1-weighted images and low signal intensity on T2-weighted images. Mucinous borderline tumor of the ovary with a large solid component is very rare, but it is clinically important to recognize the possibility of mucinous borderline tumor to avoid unnecessary surgical intervention.